Duodenal Ulcer in Children (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
This article explores the clinical course, diagnostic approaches, and treatment of duodenal ulcer in children. The findings indicate that although the disease is rare in pediatric populations, it presents significant diagnostic and therapeutic challenges. Factors such as gastric acid secretion, body weight, and age play a crucial role in the development and severity of the disease.